2012
DOI: 10.1177/1352458512445407
|View full text |Cite
|
Sign up to set email alerts
|

Acute demyelinating lesions with restricted diffusion in multiple sclerosis

Abstract: Background and objectives It is widely accepted that typical acute demyelinating lesions in relapsing–remitting multiple sclerosis (RRMS) exhibit vasogenic edema with increased diffusion, as demonstrated by an increased apparent diffusion coefficient on MRI. In contrast, acute ischemic lesions demonstrate cytotoxic edema with restricted diffusion. Recent reports have documented selected cases of acute demyelinating lesions exhibiting restricted diffusion (ADLRD) in MS. We aimed to assess the morphologies, dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
(44 reference statements)
0
28
0
1
Order By: Relevance
“…10,19 However, at times, an acute demyelinating lesion may also have areas of low ADC values, which makes it difficult to differentiate from tumors. 20 Cha et al 21,22 summarized the perfusion MR imaging features of brain tumors. The typical PWI feature of PCNSL is low relative CBV compared with that of high-grade gliomas and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…10,19 However, at times, an acute demyelinating lesion may also have areas of low ADC values, which makes it difficult to differentiate from tumors. 20 Cha et al 21,22 summarized the perfusion MR imaging features of brain tumors. The typical PWI feature of PCNSL is low relative CBV compared with that of high-grade gliomas and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…97 However, during a short and very early phase of lesion evolution (first few hours or days), transient diffusion restriction (high signal intensity on DWI and reduced apparent diffusion coefficient) has been described in some acute MS lesions. [98][99][100][101] This feature might result from an inflammatory process that leads to local hypercellularity, or from a hypoxic-ischaemic event that induces cytotoxic and vasogenic oedema. As this phenomenon only occurs in a subset of acute MS lesions, 98 DWI cannot replace contrast-enhanced T1-weighted images for differentiating between acute and chronic lesions.…”
Section: Follow-up Examinationsmentioning
confidence: 99%
“…A recent study of 13 such plaques demonstrated that the majority of the lesions were symptomatic, enhancing and periventricular in location, and all of the lesions ultimately demonstrated increased ADC values on follow-up [75]. Although it is not clear why some multiple sclerosis plaques demonstrate restricted diffusion, it has been observed that glutamate is increased in the cerebrospinal fluid of patients with acute multiple sclerosis and that macrophages and microglia produce high levels of glutamate near areas of axonal damage [76,77].…”
Section: Multiple Sclerosismentioning
confidence: 99%